Curriculum Models and Pedagogical Strategies in Hospital Schools: A Systematic Literature Review in the Context of Education - Amiruddin, Muhammad Al Afiq; Ajmain @ Jima’ain, Muhammad Talhah; Yusoff, Afiq Fadhlullah; Surjana, Afiq Afnan (Journal of Research, Innovation, and Strategies for Education (RISE), 2025)
This study aims to identify curriculum models and pedagogical strategies that have been implemented in the context of School in Hospital (SiH) through a Systematic Literature Review (SLR) approach. SiH serves as an alternative educational initiative that provides continuous learning opportunities for students undergoing long-term treatment in hospitals. However, the implementation of teaching and learning (T&L) in SiH faces unique challenges that require flexible, adaptive, and therapeutic approaches. This study adopted the PRISMA protocol and involved searches across three major databases (DOAJ, ERA, and ERIH PLUS), yielding 133 articles. After a screening process, 11 articles were selected for in-depth analysis using thematic analysis. The findings indicate that the curriculum models used in SiH emphasize content adaptation, individualized learning pathways, and the emotional well-being of students. Effective pedagogical strategies include reflective approaches, edutainment, bibliotherapy and the integration of technology such as SMART and TPACK frameworks. The study also identifies several implementation challenges, including resource constraints, emotional stress among teachers and the need for cross-sector collaboration between education and healthcare. This review highlights the need for a holistic, flexible, and contextually relevant PdPc model to ensure the sustainability and effectiveness of hospital-based education in the future.